2006
DOI: 10.1002/ijc.21712
|View full text |Cite
|
Sign up to set email alerts
|

The role of folate receptor α in cancer development, progression and treatment: Cause, consequence or innocent bystander?

Abstract: Folate receptor a (FRa) is a membrane-bound protein with high affinity for binding and transporting physiologic levels of folate into cells. Folate is a basic component of cell metabolism and DNA synthesis and repair, and rapidly dividing cancer cells have an increased requirement for folate to maintain DNA synthesis, an observation supported by the widespread use of antifolates in cancer chemotherapy. FRa levels are high in specific malignant tumors of epithelial origin compared to normal cells, and are posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
351
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(361 citation statements)
references
References 103 publications
6
351
0
4
Order By: Relevance
“…It is therefore evident that the difference in sensitivity to pemetrexed in cell lines is not due to the presence of FRa and the uptake of pemetrexed into the cells through FRa. A review on FRa (Kelemen, 2006) suggests that further research into the presence of FRa in tumours is necessary, as there is a lack of clinical studies using tumour samples, particularly in the context of pemetrexed trials. Until recently, there has been no antibody available to detect FRa by immunohistochemistry in paraffin-embedded tumour samples, although the antibodies Mov18 and Mov19 could be used on frozen sections (Bueno et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore evident that the difference in sensitivity to pemetrexed in cell lines is not due to the presence of FRa and the uptake of pemetrexed into the cells through FRa. A review on FRa (Kelemen, 2006) suggests that further research into the presence of FRa in tumours is necessary, as there is a lack of clinical studies using tumour samples, particularly in the context of pemetrexed trials. Until recently, there has been no antibody available to detect FRa by immunohistochemistry in paraffin-embedded tumour samples, although the antibodies Mov18 and Mov19 could be used on frozen sections (Bueno et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…5 CK2 activity is elevated in many kinds of tumors. 6,7 Very specific inhibitors of CK2 have been developed. In previous experiments, we showed that one of these inhibitors, 4,5,6,7-tetrabromobenzimidazole (TBB), inhibited the growth of malignant pre-B lymphoblastic leukemia cells that express Bcr/ Abl P190.…”
Section: Figurementioning
confidence: 99%
“…DMAT has the lowest K(i) value of all known CK2 inhibitors, and is cell permeable. 8 Based on reported ranges of efficacy, 7,8 DMAT was tested at 5, 10 and 20 mM. We used the previously described PLC1 cell line, which was established from a P190 Bcr/Abl transgenic mouse that developed pro/pre-B lymphoblastic leukemia/lymphoma.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Effect may be dose dependent (23) Potential stimulation of bone marrow (52) › Risk of cancer-cell stimulation in dose higher than RDA (53) Theoretically, partial reversal of antifolate therapy, e.g. Methotrexate (56) Inositol Evidence inconsistent (29) .…”
Section: -Hydroxytryptophanmentioning
confidence: 99%